1989
DOI: 10.1093/oxfordjournals.aje.a115404
|View full text |Cite
|
Sign up to set email alerts
|

Memory of Food Intake in the Distant Past

Abstract: Long term recalls of dietary intake are frequently used in case-control studies, but their validity and reliability have not been established. In this study, 91 middle-aged adults (median age, 50 years) who were participants in the Longitudinal Study of Child Health and Development at the Harvard School of Public Health in Boston, Massachusetts, starting in the early 1930s, were asked in 1984-1985 to report present food intake and to recall food intakes at ages 5-7 years. 18 years, and 30 years using food freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
7

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 0 publications
3
50
1
7
Order By: Relevance
“…However, participants might still have recalled a more recent food consumption pattern. 26 Our results may not be generalizable to women and populations that do not smoke, drink or do both to excess. Significant associations of flavonoid subclasses, population subgroups and histological subtypes of esophageal cancer might have arisen by chance because of multiple comparisons.…”
Section: /170mentioning
confidence: 71%
“…However, participants might still have recalled a more recent food consumption pattern. 26 Our results may not be generalizable to women and populations that do not smoke, drink or do both to excess. Significant associations of flavonoid subclasses, population subgroups and histological subtypes of esophageal cancer might have arisen by chance because of multiple comparisons.…”
Section: /170mentioning
confidence: 71%
“…Most studies validating recall of past diet have looked at diet in earlier adulthood and few studies have validated recall of diet in childhood 23 . Dwyer et al 24 used data from the Harvard Longitudinal Study of Child Health and Development and found that for participants with median age 50 years, the median correlation for individual food items, between actual and recalled intakes, was 0.24 for age 30 years, 0.12 for age 18 years and 0.12 for ages 5-7 years. In the Nurses' Health Study, the reproducibility and validity of adult recall of adolescent diet gave correlations of r 5 0.65 (range, 0.50-0.77) and r 5 0.40 (range, 0.13-0.59), respectively, when assessing nutrient intakes based on mothers' recalled intakes as reference 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the same women over a 15 y interval the correlation coefÂźcient was extremely low (70.03). Dwyer et al (1989) measured the correlation coefÂźcient of dairy food intake over a 25 y interval between age 30±55 y in 91 adults. They found a correlation of 0.28, as did Byers et al (1983) for milk.…”
Section: Trackingmentioning
confidence: 99%